Experimental Evidence That Permafrost Thaw History and Mineral Composition Shape Abiotic Carbon Cycling in Thermokarst-Affected Stream Networks - Zolkos, Scott; Tank, Suzanne E. (Frontiers in Earth Science, 2020)
Mounting evidence suggests that biogeochemical processing of permafrost substrate will amplify dissolved inorganic carbon (DIC=E[CO2,HCO3–,CO32–]) production within Arctic freshwaters. The effects of permafrost thaw on DIC may be particularly strong where terrain subsidence following thaw (thermokarst) releases large amounts of sediment into fluvial networks. The mineral composition and chemical weathering of these sediments has critical yet untested implications for the degree to which streams represent a source of CO2 to the atmosphere versus a source of bicarbonate to downstream environments. Here, we experimentally determine the effects of mineral weathering on fluvial CO2 by incubating sediments collected from three retrogressive thaw slump features on the Peel Plateau (NWT, Canada). Prehistoric warming and contemporary thermokarst have exposed sediments on the Peel Plateau to varying degrees of thaw and chemical weathering, allowing us to test the role of permafrost and substrate mineral composition on CO2:HCO3– balance. We found that recently-thawed sediments (within years to decades) and previously un-thawed diamicton from deeper permafrost generated significant solutes and DIC. These solutes and the mineralogy of sediments suggested that carbonate weathering coupled with sulfide oxidation was a net source of abiotic CO2. Yet, on average, 30% of this CO2 was converted to bicarbonate via carbonate buffering reactions. In contrast, the mineralogy and geochemical trends associated with sediments from the modern and paleo-active layer, which were exposed to thaw over longer timescales, more strongly reflected silicate weathering. In treatments with sediment from the modern and paleo-active layer, minor carbonate and sulfide weathering resulted in some DIC and net CO2 production. This CO2 was not measurably diminished by carbonate buffering. Together, these trends suggest that prior exposure to thaw and weathering on the Peel Plateau reduced carbonate and sulfide in upper soil layers. We conclude that thermokarst unearthing deeper tills on the Peel Plateau will amplify regional inorganic carbon cycling for decades to centuries. However, previously-undocumented CO2 consumption via carbonate buffering may partly counterbalance CO2 production and release to the atmosphere. Regional variability in the mineral composition of permafrost, thaw history, and thermokarst intensity are among the primary controls on mineral weathering within permafrost carbon-climate feedbacks.